2010
DOI: 10.1097/eja.0b013e328332845a
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses and airway complications following awake nasal intubation with blind intubation device and fibreoptic bronchoscope: a randomized controlled study

Abstract: Both FOB and BID caused similarly slight cardiovascular responses during awake nasotracheal intubation in normotensive adults. The intubation-associated airway complications were similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
1
15
1
Order By: Relevance
“…Intubation associated airway complication were similar in a study done by Sun et al [7]. In a study done by Woodall et al [10] showed out of 180 subjects 20 had upper airway trauma during Fibreoptic intubation (10%).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Intubation associated airway complication were similar in a study done by Sun et al [7]. In a study done by Woodall et al [10] showed out of 180 subjects 20 had upper airway trauma during Fibreoptic intubation (10%).…”
Section: Discussionsupporting
confidence: 65%
“…However, this was in contrast to study done by Sun et al [7], Smith et al [8] which showed no significant difference in blood pressure and heart rate between the two groups (p=0.13). This inter study difference may be related to their use of intravenous sedation prior to intubation which causes decrease in rise of mean arterial pressure and heart rate.…”
Section: Discussioncontrasting
confidence: 55%
“…This indicated that the ventilation hole might be under the glottis and, thus, we pulled the oesophagus airway out slightly. 17,18 A bright, well circumscribed circle of glow in the midline at the level of the laryngeal prominence and disappearance at the level of the suprasternal notch indicated that the lighted catheter had passed through the glottis. 3,8,17,18 Third, the battery cell was detached, and the oesophagus airway was removed carefully.…”
Section: Methodsmentioning
confidence: 98%
“…The questionnaire assessed nasal pain, sore throat and hoarseness on a 10-point visual analogue pain scale (VAS: 0 ¼ none, 10 ¼ worst). 18,20 Statistical analysis Sample size estimations were based on differences in MAP and HR. A difference of 20 mmHg or 20 beats/min in MAP or HR was considered clinically important.…”
Section: Methodsmentioning
confidence: 99%
“…Haemodynamic responses, airway injuries, hypoxia, hypercarbia, bronchospasm and respiratory depression are well recognized hazards of patients during awake nasal intubation. Hemodynamic responses to tracheal intubation may cause adverse cardiovascular events in patients with or without cardiovascular disease 7 . In our study, we have compared fibre optic and blind nasal intubation in cases of temporo mandibular joint ankylosis in terms of time for intubation, number of attempts, hemodynamic changes and complication rate in both the groups.…”
Section: Discussionmentioning
confidence: 99%